Comparative Transcriptome Analysis of Latex Reveals Molecular Mechanisms Underlying Increased Rubber Yield in Hevea brasiliensis Self-Rooting Juvenile Clones - Li, Hui-Liang; Guo, Dong; Zhu, Jia-Hong; Wang, Ying; Chen, Xiong-Ting; Peng, Shi-Qing (Frontiers in Plant Science, 2016)
Rubber tree (Hevea brasiliensis) self-rooting juvenile clones (JCs) are promising planting materials for rubber production. In a comparative trial between self-rooting JCs and donor clones (DCs), self-rooting JCs exhibited better performance in rubber yield. To study the molecular mechanism associated with higher rubber yield in self-rooting JCs, we sequenced and comparatively analyzed the latex of rubber tree self-rooting JCs and DCs at the transcriptome level. Total raw reads of 34,632,012 and 35,913,020 bp were obtained from the library of self-rooting JCs and DCs, respectively, by using Illumina HiSeq 2000 sequencing technology. De novo assemblies yielded 54689 unigenes from the library of self-rooting JCs and DCs. Among 54689 genes, 1716 genes were identified as differentially expressed between self-rooting JCs and DCs via comparative transcript profiling. Functional analysis showed that the genes related to the mass of categories were differentially enriched between the two clones. Several genes involved in carbohydrate metabolism, hormone metabolism and reactive oxygen species (ROS) scavenging were up-regulated in self-rooting JCs, suggesting that the self-rooting JCs provide sufficient molecular basis for the increased rubber yielding, especially in the aspects of improved latex metabolisms and latex flow. Some genes encoding epigenetic modification enzymes were also differentially expressed between self-rooting JCs and DCs. Epigenetic modifications may lead to gene differential expression between self-rooting JCs and DCs. These data will provide new cues to understand the molecular mechanism underlying the improved rubber yield of Hevea brasiliensis self-rooting clones.